A review of the revolutionary impact of MXene marvel in perovskite solar cells - Mohamed Sufiyan K T; Prabakaran Karupppanan (Chemical Physics Impact, 2024)
In recent years, the application of perovskites in photovoltaic and associated sectors has been experienced remarkable accomplishments. Despite the significant progress made so far, there are still challenges to overcome to enhance the performance of perovskites and address the stability issues, which are crucial for their successful commercialization in the future. The utilization of a novel two-dimensional (2D) material called MXenes in solar energy applications was introduced in 2018. The presence of MXenes in solar cells demonstrated the remarkable properties such as carrier mobility, electrical conductivity, high transparency, exceptional mechanical strength, and adjustable work function. Due to the availability of various transition elements and surface-terminating functional groups, MXene exhibits the remarkable capability to adjust the work function. This characteristic plays a crucial role in achieving appropriate band energy orientation between charge transport layers and the absorber layer in perovskite solar cells (PSCs), facilitating efficient extraction and collection of charge carriers. Consequently, this review aims to extensively examine the diverse advantages offered by MXenes. It provides a comprehensive analysis of their applications and progress in PSCs across various roles, including as additives, electron/hole transporting layers, interfacial engineering layers, and electrodes. Furthermore, this review elucidates the underlying mechanisms behind these applications, offering a comprehensive understanding of MXene contributions to the field of PSCs.